A novel robotic colonoscopy system integrating feeding and steering mechanisms with self-propelled paddling locomotion: A pilot study. (February 2021) - Kang, Myungsung; Joe, Seonggun; An, Taeyoung; Jang, Hoon; Kim, Byungkyu
Abstract: Colonoscopy is a common procedure to perform advanced therapies such as Endoscopic Submucosal Dissection (ESD), which allows for greater diagnostic specificity and sensitivity compared to other types of examination. Nevertheless, since the colonoscope can cause patient discomfort or pain due to improper manipulation, it is quite challenging for endoscopists who need to develop the necessary skills to accurately perform the procedure and minimize this discomfort. To overcome these sorts of limitations inherent in conventional colonoscopies, various studies regarding robotic and automated systems have been made. In this paper, based on the mechanics of paddling locomotion, a fully self-propelled robotic colonoscope is proposed, then integrated with assistance modules. The feeding and the steering module aim to assist the navigation of the human colon. By building on operations already familiar to endoscopists ( i.e., tip deflection, push forward and pull back, hooking, etc.), the device's automatic sequences are investigated to ensure high safety and maneuverability. In addition, a Multimodal Robotic Colonoscope Interface (MRCI) is integrated with each modular mechanism, which allows endoscopists to monitor kinetic/kinematic data and implement manual control in case of unexpected emergency ( i.e., deadlocked in colon, paradoxical movement, etc.). With the integrated interface, a pilot study using a porcine colon was conducted. Through an In-vitro test along a straight path, the velocity of the proposed RC was identified as 16.9 mm/s at a paddling frequency of 2 Hz with feeding force of 10 N. These results are 1.7 times faster (9.6 mm/s) than tests that only used paddling locomotion without any feeding force and steered angle. Furthermore, at a curved path with a radius of 60 mm, the RC velocity was measured at 21.5 mm/s, and experienced a radial elongation ratio of 20%. Similarly, at an inclined path of 30°, the velocity of the robot increased 25% (8.93 mm/s) compared to paddling locomotion alone (7.14 mm/s). The final results showed that the integrated system had superior results compared to previous studies based on self-propelled locomotion alone.